Evaluation and Development of Building Material Sales Information System to Improve Inventory Management and Customer Service - Loso Judijanto (Westscience Press, 2024)
This research investigates the Evaluation and Development of Building Material Sales Information Systems (BMIS) to Enhance Inventory Management and Customer Service within the construction industry. Through a qualitative analysis approach, the study explores the challenges faced by building material suppliers, identifies the requirements for effective BMIS, and evaluates the impacts of BMIS implementation on inventory management practices and customer service. Data were collected through interviews, focus group discussions, and case studies with stakeholders representing diverse perspectives within the construction supply chain. The findings highlight the critical role of BMIS in addressing inventory management challenges, improving order accuracy, and enhancing communication with customers. The study contributes to the development of practical recommendations for building material suppliers seeking to optimize their operations and deliver superior service experiences to their clientele.